Parallel kinetic resolution of acyclic γ-amino-α,β-unsaturated esters: application to the asymmetric synthesis of 4-aminopyrrolidin-2-ones. - Davies, S; Lee, J; Roberts, P; Thomson, J; Yin, J (2012)
Conjugate addition of a 50:50 pseudoenantiomeric mixture of lithium (R)-N-benzyl-N-(α-methylbenzyl)amide and lithium (S)-N-3,4-dimethoxybenzyl-N-(α-methylbenzyl)amide to a range of racemic acyclic γ-amino-α,β-unsaturated esters (derived from the corresponding α-amino acids) effects their efficient parallel kinetic resolution, allowing the preparation of enantiopure β,γ-diamino esters. The β,γ-diamino ester products of these reactions are readily converted into the corresponding substituted 4-aminopyrrolidin-2-ones via N-debenzylation and cyclization.